Hydrocarbon degradation test among the microbial community in oil-contaminated soil of power generators in Kerbala city, Iraq - Al-Hisnawi, Ali A. Abid; Yasser, Yass Kudhir; Kadhum, Najeh Hashem; Mustafa, Jassim M. (Iraqi Journal of Science, 2022)
The present study was designed to isolate the microbial community from oil-contaminated sites and other non-oil-contaminated sites which served as control samples in Kerbala city. In addition to test the effect of hydrocarbons on the growth of some types of bacteria. Bacterial genera and species were identified based on their growth on nutrient agar and blood agar as well as biochemical tests. According to the high bacterial growth rate on crude oil, 5 bacterial isolates were selected for further study. Growth of some identified bacteria in Minimal salt medium amended with hydrocarbon as the sole carbon source was investigated. Acinetobacter sp., Pseudomonas aeruginosa, Pseudomonas fluorescens, Pantoea sp., Pasteurella pneumonia / haemolytica, Chryseobacterium meningosepticum, Bordetella sp., and Enterobacter cloacae were the dominant phyla among all the soil samples. Although all tested bacteria were able to grow on mineral liquid media, P. aeruginosa had the most capacity for growth in this media.The present study showed that selected bacteria were able to grow and utilize MSM that contains different concentrations of gasoline. From this data, it can be concluded that oil-degrading bacteria are abundant in soils contaminated with spent oil. Consequently, these data suggest that these microbes could be useful for their application in the biodegradation of contaminated soils.